A Legal Analysis of Breach of Contract in Relation to Contract Law and Agreement Law : (Case Study of Supreme Court Decision No. 5273 K/Pdt/2024) - Michael Matondang, Ahmad; Khomaini; Robiyanti, Dewi (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to legally analyze the concept of default in insurance contracts, focusing on the application of the principle of pacta sunt servanda and the legal implications of insurance claim rejections, as reflected in Supreme Court Decision Number 5273 K/Pdt/2024. The research method used is a normative legal approach with a case study approach, through a study of laws and regulations (including the Civil Code, Law No. 40 of 2014 concerning Insurance, and POJK No. 69/POJK.05/2016), court decisions, and a literature review of various legal references. The results of the study indicate that defaults in insurance contracts, particularly in claim payments, result in significant losses for the insured and violate the principle of pacta sunt servanda. The Supreme Court decision affirms that insurance companies are obligated to fulfill all obligations agreed upon in the policy. Therefore, in the event of default, the injured party has the right to demand compensation or fulfillment of obligations in accordance with applicable law. These findings provide an important contribution to the development of contract and agreement legal theory, as well as providing a basis for improving dispute resolution mechanisms in insurance practices to protect consumer rights. This research is expected to provide a reference for legal practitioners, regulators, and academics in addressing default issues and increasing transparency and accountability in insurance contractual relationships.